Javanese Wisdom: Life-Cycle Batik as BIPA Teaching Material with Portfolio Writing Models - Diadara, Nova; Yulianeta, Yulianeta; Halimah, Halimah (IJORER : International Journal of Recent Educational Research, 2026)
The Javanese people created some batik patterns depicting the human life-cycle, from birth to death. These motifs have high cultural and philosophical value. They are also used in important ceremonies throughout the human life-cycle. This cultural richness can be integrated into BIPA (Indonesian for Foreign Speakers) learning. This study aims to design a strategy for integrating Javanese life-cycle batik into BIPA learning with portfolio writing models. This study employs a descriptive research approach with a qualitative focus. Data for this study was collected through observations at a reputable cultural museum, interviews with guides, documentation of batik motifs and literature on Javanese life-cycle batik. To ensure the validity and credibility of the data, triangulation techniques were employed. The results indicate that the life-cycle batik comprises 16 motifs used in seven traditional ceremonies marking stages of the human life-cycle. This diversity of life-cycle batik can be integrated into BIPA teaching materials using Notion as the medium. These materials cover vocabularies (40 words), as well as listening, speaking, reading and writing, and Indonesian cultural awareness. This study contributes to the development of alternative BIPA teaching materials that integrate culture. Integrating Javanese batik motifs representing the life-cycle into BIPA learning could enhance cross-cultural understanding and contextual language skills.